Utilization of acid hydrolysate of recovered bacterial cell as a novel organic nitrogen source for L-tryptophan fermentation. Issue 1 (1st January 2019) - Xu, Qingyang; Bai, Fang; Chen, Ning; Bai, Gang
ABSTRACT: In this study, waste bacterial cell (WBC) was recovered and used as an alternative to yeast extract in L-tryptophan fermentation. The effects of sulfuric acid concentration and temperature on the hydrolysis of WBC were optimized and the amino acid content in the waste bacterial cell hydrolysate (WBCH) was increased. Plackett-Burman and Box-Behnken design analysis revealed the optimum composition of the WBCH-based fermentation medium to be 22.47 g/L WBCH, 2.26 g/L KH2 PO4, and 1.25 mg/L vitamin H. L-tryptophan yield and productivity with WBCH as the nitrogen source were 52.3 g/L and 2.16 g/L/h, respectively, which were 13% and 18% higher than those obtained with the yeast extract as the nitrogen source. In addition, WBCH did not affect the growth of Escherichia coli during L-tryptophan fermentation. Cost accounting showed that WBCH could be used as a novel and cheap organic nitrogen source for industrial L-tryptophan production.